Dietary collagen peptides alleviate exercise-induced muscle soreness in healthy middle-aged males: a randomized double-blinded crossover clinical trial - Kumiko Kuwaba; Masashi Kusubata; Yuki Taga; Hiroshi Igarashi; Koichi Nakazato; Kazunori Mizuno (Journal of the International Society of Sports Nutrition, 2023)
Background Post-exercise muscle soreness and fatigue can negatively affect exercise performance. Thus, it is desirable to attenuate muscle soreness and fatigue and promote recovery even for daily exercise habits aimed at maintaining or improving health. Methods This study investigated the effects of dietary collagen peptides (CPs) on post-exercise physical condition and fitness in healthy middle-aged adults unfamiliar with exercise. Middle-aged males (n = 20, 52.6 ± 5.8 years) received the active food (10 g of CPs per day) or the placebo food for 33 days in each period of the randomized crossover trial (registered at the University Hospital Medical Information Network Clinical Trials Registry with UMIN-CTR ID of UMIN000041441). On the 29th day, participants performed a maximum of five sets of 40 bodyweight squats. Muscle soreness as the primary outcome, fatigue, the maximum knee extension force during isometric muscle contraction of both legs, the range of motion (ROM), and the blood level of creatine phosphokinase (CPK) and lactate dehydrogenase (LDH) were assessed before and after the exercise load. Results The analysis set was the per-protocol set (n = 18, 52.6 ± 6.0 years) for efficacy and the full analysis set (n = 19, 52.8 ± 5.9 years) for safety. The visual analog scale (VAS) of muscle soreness immediately after the exercise load was significantly lower in the active group than in the placebo group (32.0 ± 25.0 mm versus 45.8 ± 27.6 mm, p < 0.001). The VAS of fatigue immediately after the exercise load was also significantly lower in the active group than in the placebo group (47.3 ± 25.0 mm versus 59.0 ± 22.3 mm, p < 0.001). Two days (48 hours) afterthe exercise load, muscle strength was significantly higher in the active group than in the placebo group (85.2 ± 27.8 kg versus 80.5 ± 25.3 kg, p = 0.035). The level of CPK did not change over time. The level of LDH increased slightly but was not different between the groups. No safety-related issues were observed. Conclusions These results showed that dietary CPs alleviated muscle soreness and fatigue and affected muscle strength after exercise load in healthy middle-aged males.